DIGITAL TRANSFORMATION IS ONE OF THE MOST CRITICAL CHALLENGES AND OPPORTUNITIES FOR MODERN BUSINESSES - Roin Tateshvili (ეკონომიკური პროფილი)
This article explores the opportunities and challenges of digital transformation for small and medium-sized enterprises (SMEs) in Georgia, comparing them with the experiences of European countries.